Status of Indigenous and Minority Groups’ Rights in South Asia: A Need for a Regional Mechanism to Protect the Most Vulnerable - Chand, Anuj (Kathmandu School of Law Review, 2021)
The establishment of a regional legal mechanism for the protection of the rights of indigenous people and minority groups is a legal issue pertinent in South Asia today, especially in the context of the Rohingya persecution in the neighboring Myanmar, and the rise of the extreme right-wing regime in the largest democracy, India. Although the countries in the region have made various national level efforts to ensure the protection of the rights of these groups, the reality is that they still suffer de facto (and sometimes, de jure) discrimination. Measures, therefore, must be adopted to counter the existing discrimination. Since collective regional efforts are viewed as being ‘better suited’ for the protection of minority rights, this ‘regional’ issue can be addressed by formulation of a ‘regional’ human rights document from which a ‘regional’ complaint mechanism can emanate. For the formation of a regional human rights complaint mechanism, three key issues must be addressed. Firstly, realistic bases for the establishment of a regional mechanism must be identified. Secondly, a model for a new South Asian complaint mechanism must take into account and possibly incorporate the ‘Third World Approach to International Law (TWAIL)’. Thirdly, it is imperative to ascertain the kind of approach that will be taken with regard to the rights in question.